2020
DOI: 10.3122/jabfm.2020.06.200086
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Family Medicine Patient Retention in Opioid Medication-Assisted Treatment

Abstract: Purpose: Opioid use disorder is a prevalent and chronic condition that can lead to adverse outcomes if untreated. Medication-assisted treatment (MAT) with buprenorphine in a primary care setting has the potential to increase availability of treatment and reduce harm; however, retention in MAT is key for patient success. This study's purpose was to examine predictors of retention in a MAT program for OUD in a family medicine residency clinic. Methods: A retrospective chart review was conducted for 238 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Despite low statistical power, results suggest that MOUD provision by providers who also offer comprehensive medical care may further increase MOUD retention. These findings add support 6 for rural PCPs to offer MOUD as part of their routine comprehensive primary care to combat the opioid crisis. [10][11][12] As MOUD requires regular visits, the improved retention seen among patients receiving MOUD from their PCP may be related to the stabilizing role of longitudinal interactions with a provider.…”
Section: Discussionmentioning
confidence: 58%
“…Despite low statistical power, results suggest that MOUD provision by providers who also offer comprehensive medical care may further increase MOUD retention. These findings add support 6 for rural PCPs to offer MOUD as part of their routine comprehensive primary care to combat the opioid crisis. [10][11][12] As MOUD requires regular visits, the improved retention seen among patients receiving MOUD from their PCP may be related to the stabilizing role of longitudinal interactions with a provider.…”
Section: Discussionmentioning
confidence: 58%
“…This scoping review identified 18 studies (Figure 1) evaluating important health outcomes among patients with OUD and ADHD within addiction treatment programs. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The sample size of the included studies ranged from 12 to 81 752 patients. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The follow-up period of longitudinal studies ranged from 12 weeks to 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The sample size of the included studies ranged from 12 to 81 752 patients. 6,9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The follow-up period of longitudinal studies ranged from 12 weeks to 30 years. [24][25][26][27][28][29][30][31][32][33][34]38,39 Included in this review were 1 placebo-controlled trial, 24 5 prospective observational studies, 25,…”
Section: Resultsmentioning
confidence: 99%
“…MOUD is the gold standard treatment for OUD and is consistently associated with better OUD treatment outcomes including higher treatment retention rates and reduced substance use recurrence compared to non-pharmacological therapies for OUD [26,27], yet treatment outcomes vary widely by race, age, sex and gender, treatment setting, and polysubstance use [28,29]. Although predictors of MOUD treatment outcomes have been identified broadly [23,28,[30][31][32][33], little is known about within-group differences in Black adults receiving MOUD, especially for MOUD with buprenorphine. The few studies examining predictors of MOUD outcomes (i.e., substance use and treatment retention) among Black individuals have focused on methadone treatment samples [34,35].…”
Section: Introductionmentioning
confidence: 99%